Cardiopulmonary exercise testing – refining the clinical perspective by combining assessments. (1st September 2020) - Arena, Ross; Canada, Justin M.; Popovic, Dejana; Trankle, Cory R.; Del Buono, Marco Giuseppe; Lucas, Alexander; Abbate, Antonio
ABSTRACT: Introduction: Cardiorespiratory fitness (CRF) is now established as a vital sign. Cardiopulmonary exercise testing (CPX) is the gold-standard approach to assessing CRF. Areas covered: A body of literature spanning several decades clearly supports the clinical utility of CPX in those who are apparently health and at risk for chronic disease as well as numerous patient populations. While CPX, in and of itself, is a valid and reliable clinical assessment, combining findings with other available assessments may provide a more comprehensive perspective that enhances clinical decision making and outcomes. The current review will accomplish the following: (1) define key CPX measures based upon current evidence; and (2) describe the current evidence addressing the relationships between CPX and echocardiography, serum biomarkers, and cardiovascular magnetic resonance. Expert opinion: Cardiopulmonary exercise testing provides prognostic and diagnostic information in apparently healthy individuals, those at risk for one or more chronic conditions, as well as numerous patient populations. Moreover, if the goal of an intervention is to improve one or more systems integral to the physiologic response to exercise, CPX should be considered as a central assessment to gauge therapeutic efficacy. To further refine the information obtained from CPX, combining other assessments has demonstrated promise.